PENDEKATAN HUMAN RELATION DALAM PENGELOLAAN PROGRAM PANTI ASUHAN : STUDI KASUS DI PANTI ASUHAN FATIMAH AZZAHRA MAGELANG - Harahap, Desi Hariyanti; Mufidah, Nuril; Amrullah, Abdul Malik Karim (As-Sulthan Journal of Education, 2025)
This study aims to analyze the implementation of the Human Relations approach in program management at Fatimah Azzahra Orphanage Magelang. This approach emphasizes the importance of social and emotional relationships in the work environment as a major factor in improving performance and productivity. Using qualitative methods and a case study approach, this research examines three main aspects: staff job satisfaction and motivation, communication patterns within the organization, and informal group dynamics. The results show that staff motivation at the orphanage is driven more by emotional attachment, social recognition, and a sense of belonging, rather than solely by material incentives. Communication is two-way, open and participatory. Meanwhile, informal groups play an important role in creating a supportive and harmonious work culture. Although this approach has positive impacts, the research also found some challenges, such as the difficulty of maintaining professionalism in emotional relationships, as well as the potential for conflict in informal group dynamics. This study concludes that the application of human relations principles can strengthen the quality of services and effectiveness of social organizations if balanced with strengthening human resource capacity and reflective management.